Implementasi Sistem Manajemen Persuratan dalam Meningkatkan Kinerja Administrasi di UPT SMP Negeri 27 Medan - Tengku Darmansyah; Ovi Ardilla; Lilis Juliyanty Marbun; Lathifatun Nisa Hutabarat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Correspondence administration activities play an important role in supporting the smooth operation of the school. At UPT SMP Negeri 27 Medan, manual management of correspondence previously caused various obstacles such as delays in letter distribution and difficulties in tracking archives. Therefore, a more effective and efficient correspondence management system is needed. This study aims to describe the implementation of a correspondence management system in improving administrative performance at UPT SMP Negeri 27 Medan. This study uses a qualitative descriptive approach with observation, interview, and documentation techniques. The results of the study indicate that the process of receiving and recording incoming letters has been running according to procedures and facilitates information management. The disposition of letters is carried out systematically and on target by the school leadership. The preparation and recording of outgoing letters is carried out by paying attention to good administrative rules. In addition, archiving, maintenance, and destruction of archives have begun to be carried out digitally, thereby increasing the efficiency and speed of administrative services.